USE OF ESSENTIAL OILS IN ONYCHOMYCOSIS: AN INTEGRATIVE REVIEW (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: identify in the literature how essential oils are used in onychomycosis. Methods: integrative review with searches performed in the MEDLINE/PubMed, Web of Science, Cochrane, SCOPUS and BVS databases, with 13 studies analyzed. Results: the use of essential oils Melaleuca alternifolia, Lavandula angustifolia, Eucalyptus citriodora and Foeniculum vulgare are effective and bring benefits in the treatment of onychomycosis, as they inhibit the mycelial growth of the nail fungus. Therefore, health professionals involved in the care of people with onychomycosis must keep themselves updated on such treatment alternatives and, consequently, on improving the care provided to these patients. Conclusion: the antifungal efficacy of a variety of oils has been proven with different forms of presentation and possible associations. However, the level of evidence presented was low, which justifies the need for more robust studies on the subject.